Déjà vu and the entorhinal cortex: dissociating recollective from familiarity disruptions in a single case patient. Issue 7 (9th August 2021) - Brandt, Karen Rosemarie; Conway, Martin Antony; James, Adele; von Oertzen, Tim J.
ABSTRACT: Past research has demonstrated a relationship between déjà vu and the entorhinal cortex in patients with wider medial temporal lobe damage. The aim of the present research was to investigate this crucial link in a patient (MR) with a selective lesion to the left lateral entorhinal cortex to provide a more direct exploration of this relationship. Two experiments investigated the experiences of déjà vécu (using the IDEA questionnaire) and déjà vu (using an adapted DRM paradigm) in MR and a set of matched controls. The results demonstrated that MR had quantitatively more and qualitatively richer recollective experiences of déjà vécu. In addition, under laboratory-based déjà vu conditions designed to elicit both false recollection (critical lures) and false familiarity (weakly-associated lures), MR only revealed greater memory impairments for the latter. The present results are therefore the first to demonstrate a direct relationship between the entorhinal cortex and the experience of both déjà vu and déjà vécu. They furthermore suggest that the entorhinal cortex is involved in both weakly-associative false memory as well as strongly-associative memory under conditions that promote familiarity-based processing.